2020
DOI: 10.3390/molecules25245793
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Drp1 Sensitizes Cancer Cells to Cisplatin-Induced Apoptosis through Transcriptional Inhibition of c-FLIP Expression

Abstract: Mitochondrial fragmentation occurs during the apoptosis. Dynamin-related protein 1 (Drp1) acts as an important component in mitochondrial fission machinery and can regulate various biological processes including apoptosis, cell cycle, and proliferation. The present study demonstrates that dysfunction of mitochondrial dynamics plays a pivotal role in cisplatin-induced apoptosis. Inhibiting the mitochondrial fission with the specific inhibitor (Mdivi-1) did not affect apoptotic cell death in low concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…For example, genetic silencing of the mitochondrial BNIP3 protein or pharmacological inhibition of autophagosome formation was sufficient to re‐sensitize ovarian cancer cells to cisplatin (294). Alternatively, mitochondrial dynamics may also be exploited for the treatment of ovarian cancer, since studies have shown that inhibitors of regulatory proteins involved in mitochondrial fission enhance cisplatin‐mediated death (295). However, these approaches have not been tested in vivo , and their cancer selectivity and clinical utility remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, genetic silencing of the mitochondrial BNIP3 protein or pharmacological inhibition of autophagosome formation was sufficient to re‐sensitize ovarian cancer cells to cisplatin (294). Alternatively, mitochondrial dynamics may also be exploited for the treatment of ovarian cancer, since studies have shown that inhibitors of regulatory proteins involved in mitochondrial fission enhance cisplatin‐mediated death (295). However, these approaches have not been tested in vivo , and their cancer selectivity and clinical utility remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been shown that FIS1 is important in regulating mitochondrial autophagy and, in diabetic nephropathy, can play a protective role by participating in mitochondrial quality control through the adaptive mitochondrial autophagy pathway [ 113 ], while on the other hand, mitochondrial fission can be reduced by decreasing DRP1 expression to stop disease progression [ 114 ]. Finally, DRP1 overexpression is often associated with the presence of tumors, and, in particular, correlates with an aggressive and malignant phenotype as well as appears to be involved in the influence of tumor cell migration/invasiveness [ 115 , 116 , 117 , 118 ].…”
Section: Mitochondrial Dynamicsmentioning
confidence: 99%
“…Drp1 inhibition, either via gene silencing of Drp1 or pharmacologically using Mdivi-1, has been shown to sensitise multiple cancer cell lines to the cytotoxic effects of chemotherapeutic agents. For example, Mdivi-1 or siRNA against Drp1 enhanced cisplatin-induced apoptosis in breast carcinoma (MDA-MB-231), renal cancer cells (Caki-1), lung carcinoma (A549 and A1299), colon carcinoma (HCT116) and ovarian carcinoma (SKOV3, PA1 and A2780) [80,85,86]. Similarly, treatment with Mdivi-1 has been shown to enhance cisplatin-induced apoptosis in hepatocellular carcinomas by suppressing Drp1-mediated mitophagy [87].…”
Section: The Role Of Drp1 In Cancermentioning
confidence: 99%
“…These contradictory findings of Drp1 inhibition to act as both pro-apoptotic and anti-apoptotic events in cancers cells may be attributed to the differences in the study model employed, chemotherapeutic agents used, treatment regimens, duration of experiment, types of apoptotic stimuli applied, signalling pathways being investigated, metabolic activity of tumours and/or stage of tumourigenesis. To illustrate, in breast carcinoma MDA-MB-231 cells, Mdivi-1 enhanced the cytotoxic effect of cisplatin when cells were cultured under normoxic conditions [86] but attenuated the cytotoxic effect of cisplatin when cells were cultured under hypoxic conditions [92].…”
Section: The Role Of Drp1 In Cancermentioning
confidence: 99%